Gross Anatomical And Histomorphological Study Of Rabbit Hippocampus (Orytolaguscuniculus) - Singh, M.K.; Ghosh, R.K.; Gautam, A.K.; Singh , N.K.; Sinha, M.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Gross Anatomical and Histomorphological study of Rabbit Hippocampus (Orytolaguscuniculus) was carried out.